Developing National Occupational Standards for Behavior Analysis. Issue 2 (3rd July 2022) - Kelly, Michelle P.; Trifyllis, Irene
ABSTRACT: In order to help promote the future growth of behavior analysis, it is incumbent on behavior analysts around the world to develop country-specific standards. National Occupational Standards (NOS) are concise and readable documents that specify the knowledge an individual requires and the standard of performance that must be achieved when carrying out a specific function in the workplace. NOS are used as benchmarks of good practice across professions internationally. The current paper provides an overview of a model with 20 discrete actionable steps across five phases for developing standards: (i) preparation, (ii) development, (iii) review, (iv) validation, and (v) endorsement. A case example is provided for the development of NOS for Applied Behavior Analysts in the United Arab Emirates in the Middle East.